Interrogating the Role of Language in Clergy Sexual Abuse of Women and Girls in Zimbabwe - Nhlanhla Landan; Sindiso Zhou; Baba Tshotsho (Journal for the Study of Religion)
The abuse of women and girls by individuals in authority has been a subject of complex debates in both social and academic discourses. This article analyses the language of deception used by the clergy in winning the trust of women and girls in Christian congregations prior to abusing them. We used Feminist Critical Discourse Analysis to explore the language of religious leaders in the narrative of women and abuse as reflected in the media. Using a qualitative approach, the study analyzed 17 news articles drawn from the Zimbabwean media landscape. With these analyses, we were interested in the language used by the religious leaders as reported by the victims. Findings indicate that, to entice their victims, religious leaders rely on grooming– a persuasion process that, in the context of the clergy, invariably fuses the language of courtship, spiritual language, and religious language in order to persuade. The clergy also often used their ‘elevated’ religious position to threaten women with evil spirits and the perpetuation of their problems if they would not do as the religious leader instructed, which often led directly to sexual assault. Coupling the threats were assurances that only the pastor could rid them of their problems. This approach left the women and girls, already vulnerable due to all kinds of reasons that have brought them to seek help from the clergy in the first place, devastated and dependent on the religious leaders. The victims would thus often seek the perpetrator-to-be for his services. We conclude that the vulnerability of women and girls and their trust in the clergy expose them to exploitation, manipulation, and sexual abuse by the same religious leaders supposed to be representing purity. Further, due to the burden of poverty, unemployment, and the worsening economic environment in Zimbabwe, women remain at the risk of falling prey to the deceptive language of the sexually abusive clergy.